2006
DOI: 10.1007/11732990_17
|View full text |Cite
|
Sign up to set email alerts
|

New Methods for Detecting Lineage-Specific Selection

Abstract: Abstract. So far, most methods for identifying sequences under selection based on comparative sequence data have either assumed selectional pressures are the same across all branches of a phylogeny, or have focused on changes in specific lineages of interest. Here, we introduce a more general method that detects sequences that have either come under selection, or begun to drift, on any lineage. The method is based on a phylogenetic hidden Markov model (phylo-HMM), and does not require element boundaries to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
212
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 227 publications
(217 citation statements)
references
References 29 publications
3
212
0
2
Order By: Relevance
“…Rare SNVs that cluster within 1 kb were tagged and evaluated for mapping errors. SNVs were annotated for effect on the encoded protein and for conservation by comparison versus sequences of 43 vertebrate species (15) and orthologues in fly and worm (see Methods).…”
Section: Coupling Of Nimblegen Whole-exome Capture To Illumina Sequenmentioning
confidence: 99%
“…Rare SNVs that cluster within 1 kb were tagged and evaluated for mapping errors. SNVs were annotated for effect on the encoded protein and for conservation by comparison versus sequences of 43 vertebrate species (15) and orthologues in fly and worm (see Methods).…”
Section: Coupling Of Nimblegen Whole-exome Capture To Illumina Sequenmentioning
confidence: 99%
“…To examine whether existing uAUGs were evolutionarily conserved, we analyzed the sequence conservation of the 59 UTRs of uAUG-containing genes using alignments of four yeast genomes (Saccharomyces cerevisiae, Saccharomyces paradoxus, Saccharomyces mikatae, and Saccharomyces kudriavzevii) (http://genome.ucsc.edu). We used the phyloP score (Siepel and Haussler 2006) to evaluate the sequence conservation of each uAUG. Our data showed that in 59 UTRs, AUG was indeed the most conserved among 64 trinucleotides, with an average score of 0.72 versus 0.48 for all 64 trinucleotides in this region (Wilcoxon rank sum test, P < 7.2 3 10 À12 ).…”
Section: Genome Research 1093mentioning
confidence: 99%
“…By definition, these elements are either completely absent or have evolved swiftly in some lineages, significantly reducing the chance that we would identify them as being under constraint . To address the possibility of primate-specific constraint (other patterns of constraint gains and losses are also possible, see Supplemental Material), we used a novel algorithm to detect lineage-specific constrained sequences (Siepel et al 2006). Although our power to detect primate-specific constrained sequences is relatively weak, especially if they are short or have become constrained very recently, we found 94 such sequences (median length 164 bases; range 69-615 bases), some of which are quite striking (Supplemental Figs.…”
Section: Genome Research 767mentioning
confidence: 99%